Utilization and disposal of drilling mud waste in Libya - Kazouri, Abdelbasat (2020)
The production of oil and gas includes drilling a number of wells for exploration or production activities. During drilling operations, large volumes of drilling fluids are used to facilitate the process. In Libya, after completion of drilling operations drill cuttings and waste drilling fluids are typically discharged close to the oil fields without treatment. This can result in negative ecological impacts on the surrounding environment e.g. through infiltration of toxic constituents into soils and underground waters. In recent years, the use of sustainable technologies to remediate drilling waste has attracted greater attention and is a good choice for Libya where infrastructure and resources limit the feasibility of using conventional treatment strategies. Among the sustainable approaches available, soil stabilisation techniques e.g. solidification/stabilisation (S/S) of contaminated soil using conventional or innovative binders, and stabilisation of contaminated soil through phytoremediation using plants and grasses are promising options. In this work these two approaches were examined to test their suitability for use in Libyan Desert. The solidification/ stabilisation of drilling waste via geopolymerisation approach was tested using industrial by-products such as brick and steel industry by-products or using natural kaolin clay. The ability of the geopolymers to stabilise drilling waste by immobilising heavy metals and encapsulating hydrocarbons was evaluated through systematic experiments employing both macro properties and microstructure studies to asses: (i) the transformation of raw materials into cementitious materials; (ii) changes in physical and mechanical properties, (iii) the role of additives in enhancing the degree of geopolymerisation (iv) the leachability of solidified waste- geopolymers produced, and (v) the effect of aging for one year in Libyan Desert climate on the durability properties for produced (S/S) systems. The research has resulted in a number of key conclusions related to the feasibility of using Kaolin based geopolymers to stabilise the drilling waste generated from oil and gas industry in Libya. It is found that (S/S) systems composed from kaolin-waste geopolymer able to reduce the contaminants leachability by both physical (adsorption or encapsulation) and chemical (fixation) means, and it is possible to use Kaolin as a sustainable alternative for Portland cement in S/S system to convert the hazardous waste into inert or nonreactive hazardous waste acceptable for selected in-situ environmental engineering applications. The solidified geopolymer matrix found adequate to the requirements of sustainable waste management options such as safe landfill, reuse and recycle in the place of the generation which offering a sustainable, cost-effective approach that brings environmental and economic benefits. Phytoremediation of drilling waste contaminated soils was tested using a native Bermuda grass species. A glasshouse experiment evaluated the ability of grass to survive, uptake and/ or stabilisation of HMs and degradation of TPHs in contaminated soils. In this study, Bermuda grass was planted in soil comprising different ratios of soil: waste to examine the effect of a range of HMs and TPHs concentrations. Biomass measurements including shoot biomass, grass height, leaf area, roots height and density were made, in addition to testing for any reduction in leachability of HMs and TPHs contamination, and the role of microorganisms and enzymes in the dissipation of petroleum hydrocarbons. This research suggested that Bermuda grass is a useful species for phytoremediation of soils contaminated by drilling waste, and has the capability to stabilise the HMs in the roots and rhizosphere soils. Bermuda grass also is shown to have the potential to remediate soils contaminated by petroleum hydrocarbons when the contamination level below 7350 mg kg-1 TOC. The grass offers an environmentally-friendly, cost-effective waste management option for some sites despite requiring a longer time. Results from this study are helpful for further field phytoremediation studies.